Ziegler–Natta polymerization and the remaining challenges - Chikkali, Samir H. (Resonance, 2017)
Polymers have become indispensable in the 21st century, and today we cannot imagine life without them. However, till around the beginning of the last century, the science of polymers was considered a very primitive discipline, and majority of the scientific community did not believe that polymers even existed. Hermann Staudinger, among others, fought a long battle to convince the scientific community that polymers are real and that they are long chain molecular entities. Building on this rational bedrock of polymer science, Prof. Karl Ziegler laid the foundation of ethylene polymerization. As outlined by Dr. Sivaram in his articles on Ziegler and Natta, careful observations and systematic analyses of serendipitous results enabled Ziegler to deveop the enormously significant ‘Mulheim atmospheric polyethylene process’. A decade later, ¨ Cossee and Arlman revealed the mechanism of this polymerization reaction, which is called ‘insertion polymerization’. Insertion polymerization is popularly known as the ‘Ziegler– Natta polymerization’, in recognition of its founding fathers. Today, the world produces about 180 million tons of polyolefins annually, and polyethylene or polythene has become a household name.